Mendelian randomization analysis reveals potential association between allergic rhinitis and nasopharyngeal carcinoma - Qingfu Bao; Jianjun Zou; Changyang Wang; Haiying Wang (Discover Oncology)
Abstract Background Nasopharyngeal carcinoma (NPC) is characterized by complex interactions within its tumor microenvironment. Understanding the immune landscape and gene expression patterns is crucial for developing effective therapeutic strategies. Methods We employed multiple analytical approaches including Mendelian randomization analysis, single-cell sequencing, gene expression profiling, and spatiotemporal analysis. The study investigated associations between NPC and comorbidities, characterized immune cell populations, and analyzed gene expression patterns. Cytokine profiles and their effects on disease risk were also examined. Results The analysis revealed potential associations between NPC and both allergic rhinitis and high myopia. Single-cell sequencing identified distinct cellular populations, including three unique B cell subpopulations (M1, M2, M3) with specific molecular signatures and spatial distributions. Temporal analysis showed dynamic changes in immune cell composition: endothelial and epithelial cells dominated the early phase, B cells peaked in the middle phase, and dendritic and T cells increased in the late phase. Gene expression clustered into four main patterns, with significant roles for immune-related genes, particularly the TNFRSF family and HLA-related genes. Cytokine analysis identified IL-6 as a significant risk factor (31.4% increased risk) while IL-10 showed protective effects (8% risk reduction). Conclusions This comprehensive analysis provides detailed insights into the complex immune microenvironment and molecular mechanisms of NPC. The identification of distinct cellular populations, temporal patterns, and key molecular players offers valuable information for understanding disease progression and developing targeted therapeutic strategies.